The Relationship of the Use of Educational Game Tools (APE) with the Aspects of Children's Cognitive Development in Anarvani PAUD, Padang - Arief Fransisko; Sudarlisno Purwanto; Dewi Rahayu; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
Education game tool is a game tool that aims to develop children’s abilities, this game tool is usually used by PAUD children aged 3 to 6 years. Cognitive development has an important role in children’s success in playing a game because children’s play activities are related to thinking problems. The goals of this research to find out whether the relation between educational toys and cognitive development of early childhood in Parkit, Air Tawar Barat, Padang. Samples were taken by total sampling technique, which amounted to 7 people. The research design has taken Whatsapp interviews, and survey data collected through a questionnaire. The results of the study used moment product correlations is a relationship between APE and children’s cognitive development.Keywords: Educational Game Tools, Cognitive Development